Aspartate Aminotransferase to Alanine Aminotransferase Ratio and Arterial Stiffness in Persian Cohort Study - Sahar Sobhani; Sara Raji; Fatemeh Roudi; Mohamad Amin Bakhshali; Dina Javidjam; Effat Saghi; Zahra Ataee; Saeed Eslami Hasan Abadi (Patient Safety and Quality Improvement Journal, 2023)
Introduction Liver function tests such as AST/ALT ratio may play an important role in the progression of nonalcoholic fatty liver disease (NAFLD) and its related cardiovascular dysfunctions. The study aims to assess whether AST/ALT was associated with arterial stiffness in a large population-based cohort of apparently healthy Persian women and men.Material and Methods: To evaluate arterial stiffness non-invasively, Pulse Wave Velocity (PWV) and Augmentation Index (AI) were measured in 5031 healthy adults. Laboratory parameters, including AST and ALT, were measured after all subject's blood samples were collected. The one-way-ANOVA, the Kruskal-Wallis, and chi-square tests were used to compare the AST/ALT ratio among groups with baseline characteristics of participants following the calculation of AST: ALT through the division of AST levels by ALT levels. The univariate linear regression model was used to assess the association between mean pulse wave velocity (PWV) and AST/ALT ratio quartiles. Results: The results showed no statically significant difference in Age, HR, and MET among the different AST/ALT groups. Univariate analysis displayed that age, SBP, DBP, FBS, TG, MET, Fatty liver status, and hypertension status were positively correlated with Mean PWV. Evaluation of univariate linear regression models presented that AST/ALT has a significant correlation with Mean PWV (β = -0.139, 95% confidence interval (CI): -0.032 to -0.021, P-value < 0.001). We found that there was no linear relationship.Conclusions: According to the present study results, there was a significant negative correlation between AST/ALT with PWV. Moreover, a non-linear relationship between AST/ALT and PWV was observed as well.